INNOVACIÓN DEL RÉGIMEN JURÍDICO DE INDIGNIDAD ESTABLECIDO EN EL CÓDIGO CIVIL ECUATORIANO PARA QUE LOS HEREDEROS O LEGATARIOS, SEAN DECLARADOS INDIGNOS POR MALTRATO PSICOLÓGICO O NEGACIÓN SIN MOTIVO LEGITIMO DE ALIMENTOS AL CAUSANTE - Jiménez Mora, Bryan Andrés (2019)
The present thesis entitled: "INNOVATION OF THE LEGAL REGIME OF INDIGNITY ESTABLISHED IN THE ECUADORIAN CIVIL CODE SO THAT THE HEIRS OR LEGATEES, ARE DECLARED UNWORTHY FOR PSYCHOLOGICAL MALTREATMENT OR DENIAL WITHOUT LEGITIMATE GROUND OF FOOD CAUSING", is the product of the analysis and search of the recognition of rights enshrined in the Constitution of the Republic of Ecuador; concepts that generate importance for the elderly who are victims of psychological abuse by their heirs and legatees. This propensity, in the country has always been a subject that requires special attention by the civil inheritance regime; because the psychological abuse and illegitimate denial of food to the deceased are not considered as causes for the declaration of indignity, therefore, it is not fulfilled with what is stipulated in Article 36 of the Constitution of the Republic of Ecuador, which manifests that senior citizens will receive priority and specialized attention in the public and private spheres, especially in the fields of social and economic inclusion, and protection against violence. As with Article 3, numeral1 of the Constitution of the Republic of Ecuador, which refers to one of the primary duties of the State, such as guaranteeing without any discrimination the effective enjoyment of the rights prescribed in the Constitution and in the international instruments. The Constitution of the Republic of Ecuador, in its Article 69 guarantees the right to test and inherit as rights of freedom, as a right for the deceased and as a gratification for the care provided, but the opposite happens, when family or loved ones are seen forced by the law itself to take care of their relatives who can not do it themselves and 5 also cause them ill-treatment. For this the Ecuadorian Civil Code has an exclusion of the inheritance or legacy "the Indignity" that is the lack of merits to happen by causes foreseen in the Law, a veto to the inheritance for missing the person of the deceased. But this indignity must be declared by competent authority to take effect, however, I thought it convenient to study it and therefore conclude that it is necessary to incorporate into our civil legislation, the new causes mentioned above. With the issuance of the 2008 Constitution it was intended to repair the constant violations of which the elderly have been victims. And with that Constitution the Ecuadorian State not only called itself a State of rights and justice. In this way, it has not been possible to give plausible solutions to the current problem that older adults have always experienced. The approach of this research work would be that, the psychological abuse and the illegitimate denial of food to the deceased, are included as causes of indignity to succeed and inherit. The theoretical, legal and doctrinal gathering, as well as the application of surveys and interviews, allowed us to successfully carry out the present investigation and carry out a broad discussion on the subject, resulting in clear and precise foundations on the innovation of the legal regime of indignity established in the Ecuadorian civil code for the heirs or legatees to be declared unworthy for psychological abuse or denial without legitimate reason of food to the deceased. Therefore, I express that, within the present topic analyzed, a real and feasible solution is proposed.